Kalibrasi Pompa Injeksi Tipe In-Line Dalam Persamaan Volume Bahan Bakar Motor Diesel 4 Silinder - Hasrul Efendi; Adi Pratama Putra; Dewi Sartika (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2021)
Injector is an important component in the diesel engine fuel injection system. This study aims to obtain the results of the in-line type injection pump calibration in the equation of the fuel volume of a 4 cylinder diesel motor. The research was conducted by making simple calibration equipment. Experiments were carried out for 200-300 rpm, 350-450 rpm and 550-600 rpm experimental apparatus rotation speed. Measurements are made for the volume of fuel using a measuring cup. Injection pump calibration is done by loosening the lock on the sleeve then sliding the sleeve to the left or right on each plunger to get fuel volume similarity. The results of data collection before calibration showed the volume of fuel was 26 ml, 30 ml, 30 ml, and 28 ml. Keywords: calibration, injecton pump, in-line, diesel engine